“Chemical fingerprinting” of volcanic tephra found in Kansas using trace elements - David, Brian T. (Kansas State University, 2009)
Sedimentary beds rich in volcanic ash have been reported throughout Kansas. It is believed the source of these ashes are the large-scale eruptions from the Yellowstone Calderas. Very few of these ash units have been dated, however, and the vast majority simply reported as “Pearlette Ash.” The objective of this research was to investigate the potential of trace element geochemistry in correlating individual ash outcrops in Kansas to their eruptive source. Thirty-six previously reported ash occurrences of unknown age in Kansas were reoccupied and sampled. In addition, three unreported ash deposits were discovered and sampled. Two ash units previously identified as Huckleberry Ridge-aged and three as Lava Creek B were also collected. The samples were processed using the method of Hanan and Totten (1998) to concentrate ash shards. These ash concentrates were analyzed for specific trace and rare earth element (REE) concentrations using inductively coupled mass-spectrometry (ICP-MS) at the University of Kansas. The ash samples from known eruptions have distinct trace and REE signatures, allowing comparison to the unknown ash units. Most of the unknown ash samples correlate with specific Yellowstone eruptions. The majority of the undifferentiated “Pearlette Ash” samples correlate with the most recent Lava Creek B eruption and several unknown ashes correlate to the Huckleberry Ridge eruption. The distribution of ash units in Kansas being dominated by Lava Creek (0.60 ma) is expected because it is the most recent of the Yellowstone eruptions. The abundance of the older Huckleberry Ridge (2.10 ma) over the more recent Mesa Falls (1.27 ma) is likely the result of the much larger Huckleberry Ridge eruption.
Keywords: Rare Earth Elements; Trace Elements; Tephra; Kansas Volcanic Ash; Huckleberry Ridge Tuff; Lava Creek B Tuff; Mesa Falls Tuff; Yellowstone Plateau Volcanic Field; Geochemistry (0996); Geology (0372)